(untitled) (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
The methodology for creating porous polymeric materials based on polytetrafluoroethylene (PTFE) using NaCl, NaHCO₃, and their combinations as porogens has been studied. The influence of porogen composition on pore morphology, porous structures, and physic-mechanical properties, as well as their interdependence, has been analyzed. It has been established that NaCl forms a regular porous structure with strong inter-pore walls, while NaHCO₃, due to the destruction of these walls, promotes the formation of an interconnected porous structure with enhanced pore space connectivity but reduced mechanical strength. The combination of NaCl and NaHCO₃ as porogens creates materials with complex pore space morphology, allowing a balance between its branching and strength to be achieved. The obtained results suggest pathways for developing porous PTFE adapted to modern operational requirements for applications in filtration systems, biomedical devices, heat exchangers, and other technologically significant fields.